2009
DOI: 10.1259/bjr/61338036
|View full text |Cite
|
Sign up to set email alerts
|

Total scalp radiation using image-guided IMRT for progressive cutaneous T cell lymphoma

Abstract: Modern radiotherapy has advanced dramatically over the past decade and it is now possible to focus radiotherapy with extreme precision. This allows the radiation dose to be targeted to the area(s) of tumour while sparing adjacent normal tissues even in seemingly complicated and difficult parts of the body. The case report presented here will illustrate how it is possible to irradiate the entire scalp for extensive cutaneous T cell lymphoma while minimising radiotherapy to the underlying brain, orbits and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…[41] In the 2000s, these obstacles were partially solved with advanced technology modern RT techniques in combination with IMRT or photon-electron combination therapy techniques; problems in field composition were minimized while the target dose wrapping and dose homogeneity were improved. [41][42][43][44] As of 2009, it was observed that the TSI approach range extends from photon-electron based combined techniques to include IMRT, VMAT, tomotherapy, and high-dose rate brachytherapy. [45][46][47] When VMAT plans with the RapidArc software were implemented in 2017, it was considered as a new choice for TSI.…”
Section: Discussionmentioning
confidence: 99%
“…[41] In the 2000s, these obstacles were partially solved with advanced technology modern RT techniques in combination with IMRT or photon-electron combination therapy techniques; problems in field composition were minimized while the target dose wrapping and dose homogeneity were improved. [41][42][43][44] As of 2009, it was observed that the TSI approach range extends from photon-electron based combined techniques to include IMRT, VMAT, tomotherapy, and high-dose rate brachytherapy. [45][46][47] When VMAT plans with the RapidArc software were implemented in 2017, it was considered as a new choice for TSI.…”
Section: Discussionmentioning
confidence: 99%
“…Hem foton alanında hem de elektron alanındaki yüzey dozlarını arttırmak için 0,5 cm'lik bolus kullanılır. Teknolojik gelişmeler doğrultusunda birçok merkezde 3 boyutlu konformal radyoterapinin yerini yoğunluk ayarlı radyoterapi (YART) ve görüntü kılavuzluğunda radyoterapi (GKRT) almış olup, bu teknolojik radyoterapi yöntemleri ile hedefte daha homojen bir doz dağılımı elde edilebilmiştir (9)(10)(11) . Görüntü kılavuzluğunda radyoterapi seçenekleri arasında yer alan volümetrik ark tedavisi (VMAT) ve helikal tomoterapi (HT) karşılaştırıldığında HT'nin dozimetrik olarak üstünlüğü gösterilmiştir (12) .…”
Section: Discussionunclassified
“…Radiotherapeutic approaches to treat the entire scalp range from electron-based over photon-based to combined techniques including intensity-modulated radiotherapy (IMRT), volumetric-modulated arc therapy (VMAT), tomotherapy and high dose rate (HDR) brachytherapy [2-5]. …”
Section: Introductionmentioning
confidence: 99%